Long-day photoperiod and cool temperature induce flowering in cassava: Expression of signaling genes - Hyde, Peter T.; Setter, Tim L. (Frontiers in Plant Science, 2022)
Cassava is a staple food crop in the tropics, and is of particular importance in Africa. Recent devel-opment of genomic selection technology have improved the speed of cassava breeding; however, cas-sava flower initiation and development remains a bottleneck. The objectives of the current studies were to elucidate the effect of photoperiod, temperature and their interactions on the time of flower-ing and flower development in controlled environments, and to use RNA-sequencing to identify tran-scriptome expression underlying these environmental responses. Compared to a normal tropical day-length of 12 h, increasing the photoperiod by 4 h or decreasing the air temperature from 34/31C to 22°/19C (day/night) substantially hastened the time to flowering. For both photoperiod and temper-ature, the environment most favorable for flowering was opposite the one for storage root harvest in-dex. There was a pronounced treatment interaction: at warm day-time temperatures, percent flower-ing was low, and photoperiod had little effect. In contrast, at cooler temperatures, percent flowering increased, and long-day (LD) photoperiod had a strong effect in hastening flowering. In response to temperature, many differentially expressed genes in the sugar, phase-change, and flowering-time-integrator pathways had expression/flowering patterns in the same direction as in Arabidopsis (posi-tive or negative) even though the effect of temperature on flowering operates in the reverse direction in cassava compared to Arabidopsis. Three trehalose-6-phosphate-synthase-1 (TPS1) genes and four members of the SPL gene family had significantly increased expression at cool temperature, suggest-ing sugar signaling roles in flower induction. In response to LD photoperiod, regulatory genes were expressed as in Arabidopsis and other LD flowering plants. Several hormone-related genes were ex-pressed in response to both photoperiod and temperature. In summary, these findings provide insight on photoperiod and temperature responses and underlying gene expression that may assist breeding programs to manipulate flowering for more rapid crop improvement.